Application of QuEChERS for Analysis of Contaminants in Dairy Products: A Review - Jun Wang; Hai-yan Yang; Xin-dong Wang; Yi-fan Lv; Na Wei (Journal of Food Protection)
The safety of dairy products is intrinsically linked to consumer health, and the exceedance of risk indicators, such as pesticide and veterinary drug residues, constitutes one of the primary issues affecting their quality and safety. To assess the safety of dairy products, it is crucial to develop accurate and reliable analytical methods for their detection. Food safety testing involving important indicators such as pesticide residues, veterinary drug residues, mycotoxins, and unapproved additives has become a pivotal requirement in the industry field. The QuEChERS (Quick, Easy, Cheap, Effective, Rugged, Safe) method is widely acknowledged as a food safety analysis method currently. This method can effectively extract a wide range of compound classes from diverse matrices in food safety testing, thereby enhancing the accuracy of detection. Additionally, when combined with chromatographic-mass spectrometry techniques, it can simultaneously analyze hundreds of target analytes, rendering it widely applicable in the quality and safety testing of dairy products. Although QuEChERS has rapidly developed in the field of dairy product quality and safety analysis due to its efficiency and speed advantages, certain shortcomings remain, presenting considerable room for improvement. This paper presents a comprehensive review of the utilization and research advancements of the QuEChERS technique in dairy products, with the aim of providing more precise, expeditious, and reliable methods for the safety assessment of dairy products.